A quality innovation strategy for an inter-regional digital innovation hub - Queiroz, Jonas (2022)
Industry 4.0 is reshaping the way all the economic sectors are working. The complete adoption and understanding by the companies, large or small, of the digital transformation opportunities and benefits, requires the existence of effective instruments. Digital Innovation Hubs (DIHs) are an important instrument, strongly promoted by the European Commission, to help companies to take advantage of digital opportunities. Aiming to boost and create synergies between several DIHs and research centers located in the northern region of Portugal and Spain, and considering the disruptive ICT technologies, the establishment of an inter-regional DIH that results from the cooperation between these entities assumes a crucial importance to transform this region into an innovative pole of reference. This paper aims to describe the strategy for the management and improvement of the quality of the innovation being developed by this inter-regional DIH under the scope of the DISRUPTIVE project. Besides considering the individual strategies of the associated members, it includes cooperative aspects, regarding the sharing of knowledge, technology, and skills, aiming to improve the quality of innovation, as well as the adoption of digitization by the companies in this region.